Morphology, Conductivity and Electrochemical Properties of Hydrothermal Carbonized Porous Carbon Materials - Nagirna, N.; Mandzyuk, V. (Journal of Vasyl Stefanyk Precarpathian National University, 2016)
The paper studies the morphology, conductivity and electrochemical properties of carbon materials, obtained from raw plant materials at different condition of hydrothermal carbonization, using low-temperature porometry, impedance spectroscopy and galvanostatic charge/discharge. It is set, that in porous structure of carbon materials micropores are dominant; when carbonization temperature increased the specific surface and pore volume decrease more than 10 times. The temperature growth results in increasing the electrical conductivity of the carbon material more than 6 orders. It is found, that the maximal value of specific capacity (1138 mА·h/g) has an electrochemical system based on porous carbon carbonized at 1023 K